Penitentary Architecture - Altmann Smythe, Julio (1970)
The present work makes an approach to the historical evolution of penitentiary architecture and how it has influenced the forms of punishment or rehabilitation of inmates. The author explains that penitentiary architecture is that science that combines prison and architectural knowledge that adapts to the norms of each site. To this extent, the author compares the primitive prisons that only served to isolate and overcrowd prisoners, compared to the penitentiary architectural revolution that began in the eighteenth century, with penitentiary establishments that have a humanitarian approach and whose objective was to rehabilitate inmates. This situation allowed the implementation of various architectural systems in penitentiary centers, which are analyzed in detail in this article. In this way, the reader will be able to understand that penitentiary architecture has varied throughout history, but it has mainly reflected how such architecture has responded to the demands and needs of each era.